STUDI KRITIS TERHADAP KURIKULUM MI/SD 2013 - WASESO, HENDRI PURBO (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2017)
This paper attempts to criticize the MI/SD 2013 curriculum by using critical education theories (Paulo Freire, Michael Apple and Henry Giroux). The critical study starts from the construction process to the content contained in it. The results of this study indicate that the first, the birth of the 2013 curriculum motivated by global economic conditions where high-quality and highly competitive workforce become the main demand. Negative phenomenon that emerged in the community also became the background of the birth of the curriculum 2013. The imposition of the implementation of curriculum 2013 dominant because of political factors. Second, the construction of MI/SD 2013 curriculum can be explained through four things: the compaction of subjects in the curriculum structure of MI / SD, core competencies in the curriculum of 2013 have better character strengthening when compared with competency standards in SBC, scientific approach and integrative thematic learning for MI / SD children is designed so that learning can encourage children to master scientific skills and authentic assessment is used as an effort to measure the process and learning outcomes comprehensively. The construction of MI / SD 2013 curriculum seen from the perspective of critical education results in several conclusions: first, the objective of MI / SD 2013 curriculum leads to production relation where learners are designed to be ready and able to fill the roles that have been provided in the formation of capitalist society. In addition to research-based teacher education, the maximization of religious teaching content contained in the MI curriculum can be functioned as a language of possibility. Second, the concept contained in the MI / SD 2013 curriculum that requires learners to think high level and qualified educators precisely indicates a separation between theory and practice. This condition does not apply to urban schools. Third, MI / SD 2013 curriculum is only for children who have better capital economically, socially, and intellectually. Keywords: Curriculum MI/SD 2013 and Critical Pedagogy